2020
DOI: 10.3390/insects11100656
|View full text |Cite
|
Sign up to set email alerts
|

Social Representations of Insects as Food: An Explorative-Comparative Study among Millennials and X-Generation Consumers

Abstract: The aim of the research here presented is to describe and compare the social representations of entomophagy co-constructed and circulating among different groups of consumers. Social representations theory (SRT) allows us to understand a social reality that the individual builds based on his own experience in everyday life symbolic exchanges, whose primary function is to adapt concepts and abstract ideas using objectification and anchoring processes. We carried out this research within the structural approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 44 publications
(54 reference statements)
1
25
0
2
Order By: Relevance
“…Of the 119 studies reviewed, 52 examined gender ( 2 , 36 , 37 , 39 , 41 , 42 , 44 , 49 , 51 , 55 , 56 , 58 , 61 , 62 , 64 – 67 , 69 , 71 74 , 76 , 77 , 83 , 84 , 86 , 87 , 92 94 , 96 , 97 , 99 101 , 104 109 , 111 117 ). Of those 52 studies, 71.2% identified masculinity as a positive influence on acceptance of insects as food ( 2 , 36 , 41 , 44 , 51 , 55 , 58 , 61 , 62 , 65 – 67 , 69 , 71 , 76 , 77 , 83 , 84 , 86 , 87 , 92 94 , 96 , 97 , 99 101 , 104 , 105 , 112 , 114 , 116 , 117 ), whereas approximately one-third of those studies (34.6%) found no effect of gender ( 37 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 119 studies reviewed, 52 examined gender ( 2 , 36 , 37 , 39 , 41 , 42 , 44 , 49 , 51 , 55 , 56 , 58 , 61 , 62 , 64 – 67 , 69 , 71 74 , 76 , 77 , 83 , 84 , 86 , 87 , 92 94 , 96 , 97 , 99 101 , 104 109 , 111 117 ). Of those 52 studies, 71.2% identified masculinity as a positive influence on acceptance of insects as food ( 2 , 36 , 41 , 44 , 51 , 55 , 58 , 61 , 62 , 65 – 67 , 69 , 71 , 76 , 77 , 83 , 84 , 86 , 87 , 92 94 , 96 , 97 , 99 101 , 104 , 105 , 112 , 114 , 116 , 117 ), whereas approximately one-third of those studies (34.6%) found no effect of gender ( 37 , …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the influence of gender, many studies showed that men were more likely to accept foods made from insects ( 2 , 36 , 41 , 44 , 51 , 55 , 58 , 61 , 62 , 65 – 67 , 69 , 71 , 76 , 77 , 83 , 84 , 86 , 87 , 92 94 , 96 , 97 , 99 101 , 104 , 105 , 112 , 114 , 116 , 117 ). In addition, the results suggest that the degree of processing is crucial for the influence of gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, there are only few contributions relating youngsters and insects, and these generally focus on insects as food (e.g. Fasanelli et al, 2020;Sogari et al, 2019c), not as feed.…”
Section: Introductionmentioning
confidence: 99%
“…Beside the fundamental aspects connected to food safety and consumers’ health, recent research has shown the importance of understanding the attitudes and beliefs that determine the willingness to eat insects, directly and indirectly. In this research path, Fasanelli and colleagues [ 2 ] study—for the first time in contemporary research—the social representations that different categories of consumers have developed and hold as regards entomophagy. Using a mixed-methods approach, the authors contribute to a better understanding of consumers’ beliefs, their structure and relative importance, thus allowing insight into communication strategies.…”
mentioning
confidence: 99%